2019
DOI: 10.1038/s41422-019-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking antibody-induced CTLA-4 lysosomal degradation for safer and more effective cancer immunotherapy

Abstract: It remains unclear why the clinically used anti-CTLA-4 antibodies, popularly called checkpoint inhibitors, have severe immunotherapy-related adverse effects (irAEs) and yet suboptimal cancer immunotherapeutic effects (CITE). Here we report that while irAE-prone Ipilimumab and TremeIgG1 rapidly direct cell surface CTLA-4 for lysosomal degradation, the non-irAE-prone antibodies we generated, HL12 or HL32, dissociate from CTLA-4 after endocytosis and allow CTLA-4 recycling to cell surface by the LRBA-dependent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 50 publications
1
81
0
1
Order By: Relevance
“…In line with the idea to optimize the "on target" aspect of checkpoint blockade, Zhang et al designed and modified the pH-sensitivity of an anti-CTLA-4 antibody. 258 Because of the acidic Fig. 4 Shared transcriptional signature of inflammatory Th1 and Th17 cells and exhausted T cells.…”
Section: Tumor-specific T-cell Signaturesmentioning
confidence: 99%
“…In line with the idea to optimize the "on target" aspect of checkpoint blockade, Zhang et al designed and modified the pH-sensitivity of an anti-CTLA-4 antibody. 258 Because of the acidic Fig. 4 Shared transcriptional signature of inflammatory Th1 and Th17 cells and exhausted T cells.…”
Section: Tumor-specific T-cell Signaturesmentioning
confidence: 99%
“…The notorious side effects of anti-CTLA-4 limit its use in the clinic, but what causes the severe side effects remains largely unclear. Zhang et al [1] elucidated antibody-induced CTLA-4 lysosomal degradation as a new mechanism accounting for the severe immunotherapy-related adverse effects and limited efficacy of anti-CTLA-4 therapy.…”
mentioning
confidence: 99%
“…In a recent paper published in Cell Research, Zhang et al [1] demonstrate that antibody-induced CTLA-4 lysosomal degradation leads to irAEs and compromised efficacy. By comparing four different clones of anti-human CTLA-4 antibodies, the authors observed that irAE-prone Ipilimumab and TremeIgG1 down-regulated the CTLA-4 proteins but not for the non-irAE-prone antibodies (HL12 or HL32).…”
mentioning
confidence: 99%
See 2 more Smart Citations